Early assessment of infarct size and prediction of functional recovery by quantitative myocardial blush grade in patients with acute coronary syndromes treated according to current guidelines - Hofmann, Nina; Dickhaus, Hartmut; Erbacher, Markus; Steen, Henning; Andrassy, Martin; Loßnitzer, Dirk; Hardt, Stefan; Rottbauer, Wolfgang; Zugck, Christian; Giannitsis, Evangelos; Katus, Hugo; Korosoglou, Grigorios (Catheterization and cardiovascular interventions, 2010)
Purpose: To determine whether quantification of myocardial blush grade (MBG) during cardiac catheterization can aid the determination of follow-up left ventricular (LV)-function in patients with ST-elevation and non-ST-elevation myocardial infarction (STEMI and NSTEMI). Methods: We prospectively examined patients with first STEMI (n = 46) and NSTEMI (n = 49). ECG-gated angiographic series were used to quantify MBG by analyzing the time course of contrast agent intensity rise. Hereby, the parameter Gmax/Tmax was calculated, derived from the plateau of grey-level intensity (Gmax), divided by the time-to-peak intensity (Tmax). Cardiac magnetic resonance imaging (CMR) deemed as the standard reference for the estimation of infarct size, transmurality and of the LV-function at 6 months of follow-up. Results: Cut-off values of Gmax/Tmax=5.7/sec and 3.8/sec, respectively, yielded similar accuracy as infarct transmurality for the prediction of follow-up ejection fraction >55% (AUC = 0.86 for STEMI and AUC = 0.90 for NSTEMI, by Gmax/Tmax and AUC = 0.85 for STEMI and AUC = 0.89 for NSTEMI, by infarct transmurality, respectively, P = NS). Both clearly surpassed the predictive value of visual MBG (AUC = 0.69 for STEMI and AUC = 0.68 for NSTEMI, P < 0.05). Conclusion: Gmax/Tmax is an easy to acquire but highly valuable surrogate parameter for infarct size, which yields equally high accuracy with infarct transmurality and favorably compares with visually assessed blush grades for the prediction of follow-up LV-function in patients with acute ischemic syndromes.
Gesehen am 15.05.2023